2008
DOI: 10.4161/rna.5.2.6043
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel guide RNAs from the mitochondria ofTrypanosoma brucei

Abstract: The majority of mitochondrial mRNAs in African trypanosomes are subject to an RNA editing reaction, which is characterized by the insertion and/or deletion of U nucleotides only. The reaction creates functional mRNAs and is catalyzed by a high molecular mass enzyme complex, the editosome. Editosomes interact with a unique class of small non-coding, 3'-oligouridylated (oU) RNAs, so-called guide RNAs (gRNAs). Guide RNAs function as transacting templates in the U deletion/insertion reaction and thus, represent ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…The majority of gRNAs were identified by comparing edited mRNAs and the corresponding pseudogenes. On the other hand, direct sequencing of short RNAs from mitochondria of Leishmania tarentolae (24) and T. brucei (25,30) showed that gRNAs specifying known editing sites constitute only a fraction of the total short RNA population and that most short RNAs are uridylylated. The two established components of gRNA biogenesis, RET1 and the GRBC1/2 complex, interact in an RNA-dependent manner, and their knockdowns ablate mature gRNAs (4,44).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of gRNAs were identified by comparing edited mRNAs and the corresponding pseudogenes. On the other hand, direct sequencing of short RNAs from mitochondria of Leishmania tarentolae (24) and T. brucei (25,30) showed that gRNAs specifying known editing sites constitute only a fraction of the total short RNA population and that most short RNAs are uridylylated. The two established components of gRNA biogenesis, RET1 and the GRBC1/2 complex, interact in an RNA-dependent manner, and their knockdowns ablate mature gRNAs (4,44).…”
Section: Discussionmentioning
confidence: 99%
“…Their highly localized unwindin g mode prevents large-scale unravelling of carefully assembled RNA or RNP structures, and the efficient unwinding of short duplexes is adapted to the separation of duplexes in physiological RNAs and RNPs, which rarely exceed one helical turn. Typical examples of local unwinding are thought to occur during processes that involve guide RNAs (gRNAs), such as the unwinding of small nuclear RNA (snRNA) in pre-mRNA splicing, small nucleola r RNA (snoRNA) in ribosome biogenesis or gRNA in mitochondria l RNA editing [35][36][37][38] .…”
Section: Mitochondrial Rna Editingmentioning
confidence: 99%
“…Finally, we asked if there is evidence that published alternative gRNAs are utilized in these cells and whether editing progresses beyond these regions in a way that would allow for translation of the alternative sequence (Madej et al 2008;Koslowsky et al 2014;Madina et al 2014). The published gRNAs we include here are likely only a small fraction of total alternative gRNAs in any given cell.…”
Section: Evidence For Utilization Of Alternative Grnasmentioning
confidence: 99%
“…The sequence matching the alternative gRNA must be edited with full fidelity up to the 5 ′ end of the region covered by that alternative gRNA. Three published alternative gRNAs for RPS12 and one for ND7-5 ′ were examined in this manner (Madej et al 2008;Koslowsky et al 2014;Madina et al 2014). This analysis revealed no evidence for utilization of the ND7-5 ′ gRNA.…”
Section: Evidence For Utilization Of Alternative Grnasmentioning
confidence: 99%
See 1 more Smart Citation